Keterlibatan Orang Tua Dalam Layanan Pendidikan Anak Berkebutuhan Khusus - Opi Andriani; Aulia Nada Soraya; Novita Sari; Andre Gunawan (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This research aims to determine the involvement of parents in educational services for children with special needs. When the potential talent of a child with special needs emerges, parents are generally the first to know about it. Based on the parents' observations, everything that is in the child is then informed to the teacher so that action can be taken through a learning program for children with special needs. Through this educational program, it is hoped that they can develop their talents. The research method used is a qualitative method, and uses the library research method.